Pengaruh Firm Size Terhadap Struktur Modal Dengan Profitabilitas Sebagai Variabel Intervening (Studi pada Perusahaan Sub Sektor Jalan Tol) - Fathiah, Neneng; Khurosani, Aan; Yazid, Helmi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2018)
To participate in the government tender auction, toll road sector companies must have large capital, this makes the capital structure ratio of toll road sector companies participate in the increase. The purpose of this study to determine the effect of firm size on capital structure through profitability as intervening variable. This type of research can be categorized in quantitative research with causality design. Companies that are the subject of research are 3 companies with data every semester in the period 2008-2016 (54 observation data). The analysis used is regression with intervening variable with program Eviews version 8.0. Result of research indicate that: (1) Firm size have positive and significant effect to profitabilityof toll road sub-sector enterprises for the period of 2008-2016; (2) Firm size have positive and significant effect to capital structureof toll road sub-sector enterprises for the period of 2008-2016; (3) Profitability has a negative and significant effect on capital structureof toll road sub-sector enterprises for the period of 2008-2016; and (4) Profitability mediates the effect of firm size on capital structureof toll road sub-sector enterprises for the period of 2008-2016.